The Teacher’s Role in Telecollaborative Language Learning: The Case of Institutional Integrated Teletandem - Cavalari, Suzi M. S.; Aranha, Solange (Faculdade de Letras - Universidade Federal de Minas Gerais, 2019)
ABSTRACT Teletandeem is a model of telecollaboration in which pairs of speakers of different languages meet virtually and regularly in order to learn each other’s language. The purpose of this paper is to discuss the pedagogical implications of integrating teletandem into the foreign language syllabus, focusing on the professor’s dual role: teaching English in regular face-to-face lessons and mediating virtual autonomous and collaborative learning in teletandem. Learning diaries, produced by EFL students from a Language Teacher Education course, were collected during eight weeks of an institutional integrated teletandem project between a Brazilian and a British university. Our analysis focused on the teacher’s role in mediating foreign language learning both in the classroom and through the learning diaries. We present evidence on what the professor does so that teletandem practice can contribute to language learning in the classroom and, by the same token, how EFL lessons can aid in autonomous telecollaborative learning.

RESUMO Teletandem é um modelo de telecolaboração em que pares de falantes de duas línguas diferentes se encontram virtual e regularmente para aprenderem a língua um do outro. O objetivo deste trabalho é discutir as implicações pedagógicas de se integrar a prática de teletandem ao syllabus de uma disciplina de língua estrangeira, enfocando o duplo papel do professor: ensinar língua inglesa nas aulas presencias regulares e mediar a aprendizagem virtual autônoma e colaborativa em teletandem. Diários de aprendizagem, produzidos por estudantes de inglês como língua estrangeira de um curso de Letras, foram coletados durante oito semanas no projeto de teletandem institucional integrado entre uma universidade britânica e uma universidade brasileira. A análise tem como foco o papel do professor na mediação da aprendizagem de língua estrangeira tanto em sala de aula como nos diários. Apresentamos evidências de como a ação do professor influencia na prática de teletandem ao mesmo tempo em que as aulas de inglês auxiliam na aprendizagem telecolaborativa autônoma.
O papel do professor na aprendizagem telecolaborativa de línguas: o caso do Teletandem institucional integrado
Keywords: telecollaborative learning; institutional integrated teletandem; teacher’s role; aprendizagem telecolaborativa; teletandem institucional integrado; papel do professor